The impact of higher education attainment on women empowerment in a South African township: given the limited access to the Labour Market - Khumalo, Andiswa Sibonelo (My University, 2023)
South Africa has a significant youth unemployment problem. Youth unemployment has persistently worsened during the period of Covid-19 especially for those in remote, rural areas. While youth unemployment is high, it has worsened for women regardless of their educational attainment during and after Covid-19. Given the limited access to the labour market, this study explored the impact of higher education attainment on women’s empowerment given the weak labour market and limited employment opportunities in the remote township of Bhekuzulu in the Kwa Zulu Natal province. The findings of this qualitative study revealed that although there are limited employment opportunities women from Bhekuzulu were still positive of future employment prospects as they believed that attaining higher education made them feel independent and empowered. The study thus concludes that higher education attainment remains important even during a weakened economy with a constricted labour market because, when young women are educated, they have knowledge and are in a better position off making informed decisions about their livelihood.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts by Course Work and Research in Sociology to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2023